2020
DOI: 10.1186/s40658-020-00347-2
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and precision of zero-echo-time, single- and multi-atlas attenuation correction for dynamic [11C]PE2I PET-MR brain imaging

Abstract: Background A valid photon attenuation correction (AC) method is instrumental for obtaining quantitatively correct PET images. Integrated PET/MR systems provide no direct information on attenuation, and novel methods for MR-based AC (MRAC) are still under investigation. Evaluations of various AC methods have mainly focused on static brain PET acquisitions. In this study, we determined the validity of three MRAC methods in a dynamic PET/MR study of the brain. Method… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 59 publications
2
15
1
Order By: Relevance
“…15 Merida et al studied two atlas-based AC methods in PET/MRI studies using the specific serotonin 5-HT1A antagonist [ 18 F]MPPF, and found a performance of the multi-atlas method similar to CTAC, but also a temporal shift of the bias due to an interaction of the spatial tracer-distribution heterogeneity variation over time with the degree of accuracy of the attenuation maps using the single-atlas method. More recently, two independent PET studies on the GE SIGNA platform comparing atlas based methods and zero-echo-time (ZTE) AC using either dynamic [ 11 C] PE2I 14 or [ 18 F]FE-PE2I 30 with either CTAC or 68 Getransmission AC as reference, respectively. Both studies agree on the inferiority of atlas-based methods and a low average ZTE AC bias of striatal binding potential (BP ND ) < 2% using cerebellum as reference.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…15 Merida et al studied two atlas-based AC methods in PET/MRI studies using the specific serotonin 5-HT1A antagonist [ 18 F]MPPF, and found a performance of the multi-atlas method similar to CTAC, but also a temporal shift of the bias due to an interaction of the spatial tracer-distribution heterogeneity variation over time with the degree of accuracy of the attenuation maps using the single-atlas method. More recently, two independent PET studies on the GE SIGNA platform comparing atlas based methods and zero-echo-time (ZTE) AC using either dynamic [ 11 C] PE2I 14 or [ 18 F]FE-PE2I 30 with either CTAC or 68 Getransmission AC as reference, respectively. Both studies agree on the inferiority of atlas-based methods and a low average ZTE AC bias of striatal binding potential (BP ND ) < 2% using cerebellum as reference.…”
Section: Discussionmentioning
confidence: 99%
“…However, they diverge regarding the absolute bias, which in one study is 10% in the striatum. 14 This bias can be partially explained by the use of 68Getransmission AC instead of CTAC but remains as a point of concern primarily in the combination of quantitative data derived from different PET system, as any absolute biases will impact quantification directly when using an external reference, such as an AIF. 31 Compared to the findings in previous studies, both RESOLUTE and DeepUTE seem to provide an overall lower bias when using CTAC as the reference standard for PET attenuation, and we did not find the aforementioned temporal variation of the bias in any of the studied regions during the [ 15 O]H 2 O PET studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations